Answer: x = 0
y = -2
Explanation:
The system of equations are
-2x-4y=8 - - - - - - - - - 1
3x+y=-2- - - - - - - - - - - 2
Equation 1 and equation 2 are simultaneous linear equations.
We will use the method of elimination to solve for x and y.
In order to eliminate x, let us multiply equation 1 by 3 and equation 2 by 2. The two equations become
- 6x - 12y = 24 - - - - - - - - - -3
6x + 2y = - 4 - - - - - - - - - - 4
We would add equation 3 and equation 4. It becomes
-10y = 20
y = 20 / - 10
y = - 2
Substituting y = - 2 into equation 1, it becomes
-2x- 4 × - 2 =8
- 2x + 8 = 8
- 2x = 8 - 8 = 0
x = 0 / -2 = 0